PELAKSANAAN EKSEKUSI JAMINAN FIDUSIA BERDASARKAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR 18/PUU-XVII/2019) - Rehulina Rehulina; Andi Putra Sitorus (Ilmu Hukum Prima (IHP), 2022)
Collateral has a very important function in economic activity in general because providing capital loans from financial institutions (both banks and non-banks) requires the existence of a guarantee, which must be fulfilled by capital seekers if they want to get a loan / additional capital both for the long term and for the long term. short term, such as a fiduciary guarantee. what is the procedure for the execution of fiduciary guarantees after the issuance of the Constitutional Court Decision Number 18/PUU-XVII/2019 This research is normative legal research (legal research). The purpose of this research is to find out how to transfer fiduciary security ownership rights after the issuance of the Constitutional Court Decision Number 18/PUU-XVII/2019 which has so far transferred fiduciary security rights based on Law Number 42 of 1999 concerning Fiduciary Guarantees. Execution of executory titles, sale of objects that are objects of collateral through public auctions, underhand sales carried out based on an agreement between the Giver and the Fiduciary Recipient if in this way the highest price can be obtained that benefits the parties. However, after the issuance of the Constitutional Court's decision 18/PUU-XVII/2019, which provided a legal interpretation that the executive power of the Certificate.